2015
DOI: 10.18632/oncotarget.3981
|View full text |Cite
|
Sign up to set email alerts
|

ROS1 amplification mediates resistance to gefitinib in glioblastoma cells

Abstract: Glioblastoma (GBM) is the most aggressive brain tumor in adults and remains incurable despite multimodal intensive treatment regimens. The majority of GBM tumors show a mutated or overexpressed EGFR, however, tumors treated with tyrosine kinase inhibitors (TKIs) will inevitably recur highlighting the need to identify signalling pathways involved in GBM resistance to these drugs. To this end, we treated GBM cells that overexpress EGFR with increasing concentrations of gefitinib and isolated resistant clones. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…In non‐small‐cell lung cancer, EGFR expression level is predictive of cetuximab benefit; however, for head and neck SCC and colon cancer, even EGFR expression level is not informative in determining if cetuximab will improve patient outcome . Rather, evaluation of downstream signaling components (e.g., members of PI3K pathway) or other receptor tyrosine kinases (e.g., c‐MET, ROS1, ALK) seems to be more informative in predicting efficacy of anti‐EGFR therapy . More work is needed to determine what molecular signatures are indicative of a positive response to anti‐EGFR treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In non‐small‐cell lung cancer, EGFR expression level is predictive of cetuximab benefit; however, for head and neck SCC and colon cancer, even EGFR expression level is not informative in determining if cetuximab will improve patient outcome . Rather, evaluation of downstream signaling components (e.g., members of PI3K pathway) or other receptor tyrosine kinases (e.g., c‐MET, ROS1, ALK) seems to be more informative in predicting efficacy of anti‐EGFR therapy . More work is needed to determine what molecular signatures are indicative of a positive response to anti‐EGFR treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the lack of association between the status of KRAS mutation or EGFR positivity and therapeutic benefit of cetuximab as shown in our primary report, we strongly encourage a search for other predictive biomarkers for anti-EGFR therapy in ABTC. ROS1, ALK and c-MET, appear to be reasonable choices because the known crosstalk between EGFR signaling and all three signaling pathways, and their genetic alterations or aberrant expression may confer resistance to EGFR inhibition in NSCLC or other cancer types 24 25 26 27 28 29 . For example, c-MET activation involves the acquisition of resistance to anti-EGFR therapy via bypass of the EGFR pathway 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in wt-p53 containing cells, cyclooxygenase 2 is upregulated under genotoxic stress and DDR1 activated cyclooxygenase 2 expression by NFKB pathway, leading to the resistance of breast cancer cells to etoposide [54]. Several studies demonstrated that DDR1 expression at protein level promotes the resistance of tumor cells to chemotherapeutic drugs like etoposide in lymphoma [55, cisplastine in ovarian cancer [56] and gefitinib in glioblastoma cells (both at the protein but also at RNA level) [57]. However, molecular mechanisms by which DDR1 leads to chemotherapy resistance remain unknown.…”
Section: Ddr1mentioning
confidence: 99%